Pengaruh Pendapatan dan Beban terhadap Beban Pajak dengan Earning Before Interest and Tax sebagai Variabel Intervening - Suriani Ginting; Sonya Enda Natasha S. Pandia; Evi Juita Wailan'An (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
Tax expense is the aggregate amount of current tax expense and deferred tax expense which is calculated on accounting profit recognized in one period. This study aims to determine and analyze the effect of revenue and expenses on the tax expense with Earnings Before Income and Tax (EBIT) as an intervening in consumer goods companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The population of the study was 54 consumer goods companies with purposive sampling method obtained a total sample of 24 companies and 120 observations. Methods Data analysis uses multiple linear regression analysis and path analysis by testing the classical assumptions first. The results of the study show that EBIT is able to mediate the effect of  Rvenue  on Tax  Expense on Consumer Goods companies listed on the Indonesia Stock Exchange for the 2015-2019 Period but EBIT is not able to mediate the Effect of Expenses on Tax Expense  on Consumer Goods Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period